The concentration of NaCl soaking to decreasing cyanide levels in Gadung (Dioscorea hispida Dennst) - Kresnadipayana, Dian; Waty, Helmy Indra (Jurnal Teknologi Laboratorium, 2019)
Cyanide is one component contained in gadung tubers, and therefore, consuming gadung that contains more than 1 ppm of cyanide can cause nausea and intoxication. This research aims to study the effect of concentration variation of NaCl soaking to the decrease of cyanide levels in gadung. This research is an experimental study with three treatment. Testing is only done once. Samples of gadung were soaked by NaCl (0% 1% 3% 5%) for 3 days. Determination of cyanide content in gadung used the UV-Vis spectrophotometry method by adding Ninhydrin 0.1% in Na2CO3 2% and NaOH 0.1 % in the sample filtrate. Result of this research had shown that cyanide content in gadung before NaCl soaking was 4.42 ppm and after NaCl soaking (0% 1% 3% 5%) were 3.52; 2.53; 0.43 and 0.01 ppm, respectively.